Interaction of adolescent aspirations and self-control on wellbeing in old age: Evidence from a six-decade longitudinal UK birth cohort. Issue 6 (2nd November 2021) - Yamasaki, Syudo; Nishida, Atsushi; Ando, Shuntaro; Murayama, Kou; Hiraiwa-Hasegawa, Mariko; Kasai, Kiyoto; Richards, Marcus
ABSTRACT: Adolescent self-control is important for the pursuit of long-term goals and predicts later outcomes, but motivating self-control is essential for subjective wellbeing throughout life. We investigated long-term implications of the interaction between adolescent aspirations and self-control on subjective wellbeing in early old age. We analysed longitudinal population-based birth cohort data spanning 60 years. Data from 1, 727 participants, which were drawn from the 1946 British birth cohort, were analysed. Teachers assessed self-control and mental health in participants aged 13–15, and participants prioritised their intrinsic and extrinsic aspirations at 16. At age 60–64 years, subjective wellbeing was self-reported using the Satisfaction with Life Scale. Results revealed a significant interaction between adolescent aspirations and self-control on life satisfaction in early old age. Among adolescents with self-control problems, higher intrinsic aspirations predicted better life satisfaction. Thus, for adolescents with self-control problems, intrinsic aspirations-oriented educational and psychological approaches may improve later life satisfaction.